2012
DOI: 10.7324/japs.2012.21107
|View full text |Cite
|
Sign up to set email alerts
|

In vitro Evaluation of Antimicrobial and Cytotoxic Activities of Rosmarinus officinalis L. (Lamiaceae) Essential Oil Cultivated from South-West Tunisia

Abstract: Rosmarinus officinalis (Lamiaceae), commonly known as rosemary and iklil, is often used by North African populations for the treatment of several inflammatory and infectious diseases. This study aimed to investigate the antimicrobial and cytotoxic properties of essential oil extracted from the seeds and leaves of R. officinalis. Antimicrobial activity assays involved the determination of inhibition zones and the minimum inhibitory concentration with regards to sixteen pathogenic microbial strains, using disc d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…Similarly, cytotoxic activities of essential oils from various aromatic plants were attributed to specific components of the oils [ 36 , 37 ]. Some of the main components of A. palestina oil have previously been tested for cytotoxic properties.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, cytotoxic activities of essential oils from various aromatic plants were attributed to specific components of the oils [ 36 , 37 ]. Some of the main components of A. palestina oil have previously been tested for cytotoxic properties.…”
Section: Resultsmentioning
confidence: 99%
“…After a rigorous assessment of relevant publications, 91 studies published since 2000 were identified as eligible for inclusion in this investigation (Abu‐Darwish et al., 2012; Akarca et al., 2019; Akdemir Evrendilek, 2015; Aliakbarlu et al., 2013; Al‐Nabulsi et al., 2020; Al‐Saghir, 2009; Alizadeh Sani et al., 2017; Andleeb et al., 2014; Awaisheh, 2013; Ayala‐Zavala et al., 2013; Baali et al., 2019; Bahadori et al., 2016; Bayoub et al., 2010; Bhavya et al., 2020; Bonilla & Sobral, 2016; Boukhebti et al., 2011; Bouyahya et al., 2019; Butkhup & Samappito, 2011; Campana et al., 2017; Cansian et al., 2010; Celikel & Kavas, 2008; Ceylan et al., 2014; de Oliveira et al., 2012; Deka et al., 2016; Djenane et al., 2012; Dobre et al., 2011; Eissa et al., 2012; El Abdouni Khayari et al., 2016; Elgayyar et al., 2001; Elshafie et al., 2016; El‐Shenawy et al., 2015; Feng et al., 2017; Fernández‐López et al., 2005; Ferreira et al., 2019; Fidan et al., 2019; Frank et al., 2018; Ghabraie et al., 2016; Golestani et al., 2015; Gonelimali et al., 2018; Goñi et al., 2009; Gupta et al., 2008; György, 2010; Hayouni et al., 2008; Huang et al., 2014; Hussein et al., 2018; Ibrahim, 2014; Chobba et al., 2012; Irkin & Korukluoglu, 2009; Iseppi et al., 2019; Iturriaga et al., 2012; Keskin et al., 2010; Kim et al., 2004, 2017; Kobus‐Cisowska et al.,…”
Section: Methodsmentioning
confidence: 99%
“…Agar well diffusion method IZ = 20 mm (Tural & Turhan, 2017) Broth microdilution method MIC = 0.0313%, v/v, MBC = 0.0625%, v/v (Wang et al, 2012) Disc diffusion assay IZ = 7-38 mm, MIC = 25-75 μl/ml (Abdullah et al, 2015;Abu-Zaid et al, 2013;Chahboun et al, 2014;Djelloul, (Continues) & Hacini, 2017;Issabeagloo et al, 2012;Kazemi et al, 2012;Kesatebrhan & Tesema, 2014;Martins et al, 2012) Microdilution method IC 50 = 190 ± 5 μg/ml. MIC = 0.5-100 μg/ml, MBC = 1.5-5 μg/ml (Ben Chobba et al, 2012;Jardak et al, 2017;Kazemi et al, 2012) RAPD analysis-microdilution method MIC = 5 μl/ml, MBC = 1.25 μl/ml (Hamedo, 2009) Essential oil-rich fractions Disc diffusion assay and broth dilution assay IZ = 17-33 mm MBC = 0.25-2.25 mg/ml (Santonyo et al, 2005) reveal the potential of rosemary as a promising antimicrobial agent and foresee their effectiveness as a functional food. It is generally admitted that a substance with antimicrobial activity determined by the agar or disc diffusion method that displayed inhibition halo greater than 13 mm is active (Clinical and Laboratory Standards Institute, 2003).…”
Section: Different Leaves Extract Prepared By Supercritical Fluid Ext...mentioning
confidence: 98%
“…56, 1.56, and 3.125 mg/ml, respectively (El Kichaoui et al, 2017) et al, 2012) Broth microdilution method MIC = 0.0625%, v/v, MBC = 0.125%, v/v(Wang et al, 2012) Disc diffusion assay MIC = 25 μl/ml(Abu-Zaid et al, 2013) IZ = 8-20 mm(Chahboun et al, 2014;Djelloul et al, 2017;Kazemi et al, 2012;Kesatebrhan & Tesema, 2014;Martins et al, 2012) RAPD analysis-microdilution method MIC = 25 μl/ml, MBC = 2.5 μl/ml(Hamedo, 2009) Essential oil-rich fractions Disc diffusion assay and broth dilution assay IZ = 17-33 mm, MBC = 2.25 to 0.25 mg/ml(Santonyo et al, 2005.5, 12.5, and 25 mg/ml, respectively(El Kichaoui et al, 2017) Essential oil Disc diffusion assay IZ = 12.8-15 mm(Ben Chobba et al, 2012;Kazemi et al, 2012;Martins et al, 2012) Microdilution method IC50 = 330 μg/ml, MIC = 3-282 μg/ml, 25, 12.5 and 50 mg/ml, respectively(El Kichaoui et al, 2017) .0313%, v/v; MBC = 0.25%, v/v(Wang et al, 2012) Essential oil Disc diffusion assay and microdilution method IZ = 20 mm and MIC = 4 μg/ml(Kazemi et al, 2012) Essential oil Disc diffusion assayIZ = 18-34 mm (Abdullah et al, 2015) Essential oil-rich fractions Disc diffusion assay and broth dilution assay IZ = 17 to 33 mm, MBC = 2.25 to 0.25 mg/ml(Santonyo et al, 2005) MIC = 6.25 mg/ml, MMC = 6.25 mg/ml(de Oliveira et al, 2017) …”
mentioning
confidence: 99%